Long-Term Survival and Differentiation of Human Neural Stem Cells in Nonhuman Primate Brain with no Immunosuppression. Issue 2 (February 2015) - Lee, Sang-Rae; Lee, Hong J.; Cha, Sang-Hoon; Jeong, Kang-Jin; Lee, Youngjeon; Jeon, Chang-Yeop; Yi, Kyung Sik; Lim, Inja; Cho, Zang-Hee; Chang, Kyu-Tae; Kim, Seung U.
Cellular fate of human neural stem cells (hNSCs) transplanted in the brain of nonhuman primates (NHPs) with no immunosuppression was determined at 22 and 24 months posttransplantation (PTx) regarding survival, differentiation, and tumorigenesis. Survival of hNSCs labeled with magnetic nanoparticles was successfully detected around injection sites in the brain at 22 months PTx by MRI. Histological examination of brain sections with H&E and Prussian blue staining at 24 months revealed that most of the grafted hNSCs were found located along the injection tract. Grafted hNSCs were found to differentiate into neurons at 24 months PTx. In addition, none of the grafted hNSCs were bromodeoxyuridine positive in the monkey brain, indicating that hNSCs did not replicate in the NHP brain and did not cause tumor formation. This study serves as a proof of principle and provides evidence that hNSCs transplanted in NHP brain could survive and differentiate into neurons in the absence of immunosuppression. It also serves as a preliminary study in our scheduled preclinical studies of hNSC transplantation in NHP stroke models.